Book of reviews : Amphibians And Reptiles Of The Hashemite Kingdom Of Jordan. An Atlas And Field Guide - Das, Indraneil (Centre for Herpetology, Madras Crocodile Bank Trust, 2001)
The herpetofauna of the Hashemite Kingdom of Jordan, unlike some of neighbouring countries, suffered from a lack of an accessible field guide to its herpetofauna. Written by a well-known team of Jordanians and Moravians have rectified the situation with this excellent field guide.